Discovery of a new genus of tanaidacean (Crustacea: Tanaidacea: Mirandotanaidae) found associated with a deep-sea terebellid polychaete - Suárez-Morales, E., Londoño-Mesa, M., & Heard, R.W. (Contributions to Zoology, 2011)
Only one species of Tanaidacea, Expina typica, has been hitherto reported as an endosymbiont; it was recovered from the body cavity of deep-sea holothurians. During a survey of the deepsea benthic community in the Florida Straits off the Bahamas, Terebellatanais floridanus, a new genus and species of a tanaidomorphan tanaidacean was recovered at a depth of 545 m from the oral cavity of the terebellid polychaete Biremis blandi. Terebellatanais gen. nov. is tentatively assigned to the family Mirandotanaidae, as it appears to have affinities with Mirandotanais and Pooreotanais but also with Expina. It is distinguished from these genera by a unique combination of characters, including four antennular and antennal articles, a naked endite of the maxillipedal basis, hook-like chelipeds, the armature of the pereopods, and characters of the mouthparts. Most of the specimens of T. floridanus examined are mancas, but some were distinctly larger and with a different development of the last pereopod, thus suggesting that at least two manca stages are represented. The occurrence of the new genus and species within the oral cavity of B. blandi, its peculiar morphology, and the absence of fully grown adults, suggest that T. floridanus may be a symbiont of Biremis blandi at least during part of its development. Whether this relationship is commensal or parasitic remains to be determined.